(untitled) (Jurnal Bahasa, 2024)
The beauty of a person’s physical appearance is often associated with skin color. The perception and evaluation of contemporary society generally considers a person with black skin as an individual who does not have a beautiful appearance and is not attractive, especially for a woman. Therefore, this study highlights the symbolism of plants associated with ’black’ skin color. The methodology of this study is qualitative in which the data source is secondary data from the collection of pantun ’Kurik Kundi Merah Saga’. The approach used in this study is inquisitive semantics. It is seen to be able to unravel the community’s perception of the use of plant symbolism in the poem to reveal the views and thoughts of the previous Malay community about ’black’ skin. The study shows that the symbolism associated with plants has positive values, thoughts, Malay wisdom and hence reveals the level of intellectuality of the previous Malay society. For example, the findings in the pantun "hitam-hitam si tampuk manggis, sungguh hitam ku pandang manis" which relates the physical appearance of a person with dark skin but still likable and beautiful to be seen by the people. Furthermore, symbolism in traditional prose such as Malay pantun has a close relationship with the activities and daily life of the community. This study further expands the scope of analysis and research involving traditional prose such as Malay pantun. Keywords: Impression, beauty, inquisitive semantics, philosophy; pantun, Malay wisdom Full text: PDF